The study of Seloko Adat as safety-valve to prevent religious conflict in Jambi City, Indonesia - Abdul Halim; Pahrudin HM (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
Jambi City has the potential for social conflict, especially religious conflict related to the establishment of houses of worship. The history of religious conflict in Indonesia notes that houses of worship have always been a source of conflict which often leads to destruction and burning. Related to this, there needs to be an effort made so that this conflict is not prolonged, one option is by revitalizing the wisdom of local culture that grows in each region.This study was conducted using a qualitative research approach. This research was conducted in Telanaipura, Alam Barajo, and Kotabaru in Jambi City. The results of this study found that as a pluralistic area, Jambi City was also not spared from the conflict of the establishment of places of worship that occurred in three regions. However, the conflict that occurred was not prolonged because the people of Jambi City still adhered to the wisdom of the local culture in the form of Seloko Adat which is internalized through family, education and social environment. This internalization forms an obedient, rule-abiding and inclusive character inherent in Jambi City society. Seloko Adat is another form of contextualization of the Coser’s concept of the Safety-Valve which proved to be able to prevent the community from anarchic conflict. Since it has a significant potential to help foster peace in communities, there needs to be an understanding of Seloko Adat through a variety of activities, such as socialization in various formats and holding social activities with the theme of increasing understanding of it.